2017
DOI: 10.1002/ece3.3348
|View full text |Cite
|
Sign up to set email alerts
|

Varying congruence among spatial patterns of vascular plants and vertebrates based on habitat groups

Abstract: Proxies are adopted to represent biodiversity patterns due to inadequate information for all taxa. Despite the wide use of proxies, their efficacy remains unclear. Previous analyses focused on overall species richness for fewer groups, affecting the generality and depth of inference. Biological taxa often exhibit very different habitat preferences. Habitat groupings may be an appropriate approach to advancing the study of richness patterns. Diverse geographical patterns of species richness and their potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 56 publications
(109 reference statements)
1
13
0
Order By: Relevance
“…The RC is considered strong when the between-taxon correlation coefficient exceeds 0.5 [50]. Our results were consistent with previous studies and supported significant positive RCs between vascular plants and vertebrates in most cases [23,24,51,52], indicating that vascular plants have application value to be indicator taxa for vertebrates. Note that the effectiveness of vascular plants as indicator taxa for vertebrates varied with climatic regions and taxonomic groups (Figure 2).…”
Section: Difference Between Climatic Regions In the Effectiveness Of ...supporting
confidence: 92%
See 2 more Smart Citations
“…The RC is considered strong when the between-taxon correlation coefficient exceeds 0.5 [50]. Our results were consistent with previous studies and supported significant positive RCs between vascular plants and vertebrates in most cases [23,24,51,52], indicating that vascular plants have application value to be indicator taxa for vertebrates. Note that the effectiveness of vascular plants as indicator taxa for vertebrates varied with climatic regions and taxonomic groups (Figure 2).…”
Section: Difference Between Climatic Regions In the Effectiveness Of ...supporting
confidence: 92%
“…However, vascular plants were considered indicator taxa because they were easy to survey, widely distributed, and stable in taxonomy [15,54]. For example, at China's regional and local scales, there are significant strong RCs between vascular plants and a few taxonomic groups (vertebrates, insects), and vascular plants have been considered potential indicator taxa [23,24,39,51]. Brunbjerg et al [15] also confirmed that vascular plants are suitable indicator taxa for many taxonomic groups in Denmark (e.g., bryophytes, lichens, macro-fungi).…”
Section: Difference Between Climatic Regions In the Effectiveness Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because of the reason with the application of preprocessing unwanted or irrelevant areas can be eliminated and obtaining significant region of interest. Table 1 list the performance analysis results of accuracy, precision and recall using the proposed HFI-DRLC method and existing methods, optimization strategy for salinity stress at seedling in rice [1], GWAS and linkage mapping [2] respectively (both without and with preprocessing). All the three performance metrics are measured in terms of percentage (%).…”
Section: Performance Analysis Of Precision Recall and Accuracymentioning
confidence: 99%
“…In this section, the performance analysis in terms of MAE and prediction time using the proposed HFI-DRLC method and existing methods, optimization strategy for salinity stress at seedling in rice [1] and GWAS and linkage mapping [2] are detailed. Table 2 list the performance analysis results of prediction time and MAE using the proposed HFI-DRLC method and existing methods, optimization strategy for salinity stress at seedling in rice [1], GWAS and linkage mapping [2] respectively. The prediction time performance metric is measured in terms of milliseconds (ms) whereas the MAE is evaluated in terms of percentage (%).…”
Section: Performance Analysis Of Mae and Prediction Timementioning
confidence: 99%